Features of bicycle abreast riding and its application in bicycle facility operating evaluation and design optimization. (April 2017) - Yan, Xingchen; Zhu, Li; Chen, Jun; Wang, Tao; Ye, Xiaofei
This article aims to measure bicycle facility operating state based on the survey and analysis of bicycles' abreast riding. We conducted a detailed bicycle operating investigation consisting of four exclusive bicycle paths in Nanjing, China, and introduced an approach to extract the data of bicycle abreast riding from bicycle arrival data. Then, the relationships between bicycle volume and bicycle group size, abreast riding number, lateral clearance, and path width occupancy were discussed. In the end, we compared passing event, macro bicycle flow parameter, and single riding ratio in representing a cyclist's individual comfort, suitability, and difficulty to data acquisition. The results and conclusions we obtained are as follows: (1) bicycle group size, abreast riding, and path width availability keep a positive correlation with bicycle volume, respectively, while single riding proportion and lateral clearance have a negative relationship with it. (2) Bicycle single riding proportion is a better parameter reflecting bicycle level of service from an objective perspective. We first studied bicycle abreast riding from a vantage point of bicycle group. Single riding proportion offers bicycle facility appraisers another possible choice to assess bicycle level of service. Path width occupancy is very useful in optimizing bicycle facility.